A comparison of bivariate pseudospectral methods for nonlinear systems of steady nonsimilar boundary layer partial differential equations. Issue 6 (29th September 2020) - Mpendulo Magagula, Vusi; Motsa, Sandile S.; Sibanda, Precious
Abstract : In this work, three pseudospectral methods, namely bivariate spectral relaxation method, spectral local linearization, and bivariate spectral quasilinearization method are analyzed for steady nonlinear nonsimilar boundary layer partial differential equations. Their accuracy and general performance are discussed. A system of three nonlinear coupled partial differential equations that models an unsteady three‐dimensional MHD‐boundary‐layer flow due to an impulsive motion of a stretching surface is used to demonstrate the accuracy, convergence, and general performance of the three pseudospectral methods. The general comparison of the three pseudospectral methods is presented in graphical and tabular forms. Computational times of each method is presented in tabular form, showing the skin friction and Nusselt number.